2020
DOI: 10.1097/moo.0000000000000645
|View full text |Cite
|
Sign up to set email alerts
|

Current opinions in otolaryngology and head and neck surgery: functional considerations in reconstruction after laryngectomy

Abstract: Purpose of review To review reconstruction techniques following total laryngectomy, partial laryngopharyngectomy, and total laryngopharyngectomy with an emphasis on long-term swallow and speech outcomes. Recent findings Recent literature has shown that the use of fasciocutaneous free flaps in the reconstruction of laryngectomy defects may lead to improved speech and swallow outcomes as compared with regional or free musculocutaneous flaps. Radial forear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In the reconstruction of total laryngectomy, our study found that the ALT flap was more reliable than the peroneal flap. ALT flaps have a large skin donor site, dependable perforators, and adequate volume to fill the dead space and are simple to design with a monitor flap and phonatory tube 25,29 . The multilayer fascial underlay technique can also be used to reduce the rate of fistula formation even further 30 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the reconstruction of total laryngectomy, our study found that the ALT flap was more reliable than the peroneal flap. ALT flaps have a large skin donor site, dependable perforators, and adequate volume to fill the dead space and are simple to design with a monitor flap and phonatory tube 25,29 . The multilayer fascial underlay technique can also be used to reduce the rate of fistula formation even further 30 .…”
Section: Discussionmentioning
confidence: 99%
“…If the flap volume was insufficient to fill up the space and heal with surrounding tissue, resulting in an “empty neck,” a higher risk of leakage and late fistula formation could be expected (Figure 1 ). 17 , 25 This idea could be applied to the use of an RF flap. Many studies have found a higher risk of fistula formation in the RF flap reconstruction population, 11 , 19 , 26 which could be the reason.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reconstruction of pharyngeal defects following resection of advanced laryngopharyngeal cancer remains a challenge. Many techniques have been proposed and utilised over the years with free flap reconstruction being the current mainstay of treatment providing very good functional and cosmetic outcomes even though donor site morbidity and flap failures remains an issue [11][12][13]. Pectoralis major flap reconstruction is an alternative reconstructive option of neopharynx.…”
Section: Discussionmentioning
confidence: 99%